Insulin receptor signaling regulates actin cytoskeletal organization in developing photoreceptors - Rajala, Raju V. S. (2009)
The insulin receptor (ir) and ir signaling proteins are widely distributed throughout the cns. ir signaling provides a trophic signal for transformed retinal neurons in culture and we recently reported that deletion of ir in rod photoreceptors by cre/lox system resulted in stress‐induced photoreceptor degeneration. these studies suggest a neuroprotective role of ir in rod photoreceptor cell function. however, there are no studies available on the role of insulin‐induced ir signaling in the development of normal photoreceptors. to examine the role of insulin‐induced ir signaling, we analyzed cultured neuronal cells isolated from newborn rodent retinas. in insulin‐lacking cultures, photoreceptors from wild‐type rat retinas exhibited an abnormal morphology with a wide axon cone and disorganization of the actin and tubulin cytoskeleton. photoreceptors from ir knockout mouse retinas also exhibited a similar abnormal morphology. a novel finding in this study was that addition of docosahexaenoic acid, a photoreceptor trophic factor, restored normal axonal outgrowth in insulin‐lacking cultures. these data suggest that ir signaling pathways regulate actin and tubulin cytoskeletal organization in photoreceptors; they also imply that insulin and docosahexaenoic acid activate at least partially overlapping signaling pathways that are essential for the development of normal photoreceptors.